PENGARUH PENAMBAHAN MAIZENA PADA PEMBUATAN BISKUIT GLUTEN FREE CASEIN FREE BERBAHAN BAKU TEPUNG PISANG GOROHO (Musa Acuminate) - Lois I.V.A. Utomo; Ir. Erny Nurali, MS; Ir. Maya Ludong, MS. (Universitas Sam Ratulangi, 2017)
ABSTRACTÂ The purpose of this research was to determine the proper formula of biscuit made from goroho flour added with cornstarch; ToÂ evaluate the sensory quality of the gluten free casein free biscuits made from goroho flour and analyze the nutrition content of biscuit and calculate the calories of biscuits gluten free casein free. The research was design using complete random sampling method with four treatments : 0% , 10%, 20% and 30% added of cornstarch. The results showed the addition of cornstarch on a gluten free casein free biscuits made from goroho flour most panelist favored the addition of 20% cornstarch that contain carbohydrates 69,09%, coars fibers 0,40%, proteins 2,81%, fats 22,89%, water content and calorific value 439,61 cal.Â Keywords : gluten free casein free biscuits, goroho flour, cornstarch